THE ROLE OF HEALTH ADMINISTRATORS IN HEALTHCARE WORKFORCE PLANNING AND MANAGEMENT - Hassan Fuhaid Mohammed Alotaibi, Abdullah Sogair Gazi Almutairi, Hamoud Mujari Mohammed Al. Qahtani, Mohammed Abdullah Mohammed Almutlaq, Fawziah Mansor Ali Akam, Manal Abdulrahman Alanazi, Adel Mohammad Alrasheedi,,; Hanan Obaid Aldawsari, Ali Jamea Almutairi, Abdulrahman, Sulaiman Alrakb, Saad Mohammed Al-Bishi, Muteb Faleh Aldaghilbi, Mamdouh Saed Almutairi, Abduallh Obaid Alreshidi, (Chelonian Research Foundation, 2022)
The field of health systems is intricate and continuously changing, and there is still little knowledge on the abilities of health administrators and leaders to effectively address present and upcoming challenges. Prior research has focused on individual countries and has not included diverse international and multi-level perspectives. This paper analyzes the present and upcoming difficulties faced by health leaders and workforce managers in various settings and healthcare systems. A comprehensive review of literature pertaining to health management and leadership was undertaken, which included identifying prominent publishing platforms and devising an effective search methodology. The findings indicated that healthcare sectors worldwide face a range of persistent challenges and emerging trends in health leadership and management. To summarize, the current issues and future requirements of the worldwide medical administration workforce revolve on improving efficiency, implementing change, and effectively managing human resources. It is crucial to ensure that existing health managers and leaders has the necessary skills to effectively react to the present situation. Keywords: Health administrators, healthcare, workforce, planning, management.